Article RETRACTED due to malpractice Hidden Iron Deficiency in High-Performance Adolescents: A Multi-Omics and Predictive Analytics Framework - Natour, Amal (Retos, 2026)
Purpose: The research question of this study was to explore the multifaceted interaction between iron status, inflammation and aerobic performance in adolescent athletes as well as to establish a sophisticated, integrative model of early iron deficiency diagnosis and prediction of performance beyond conventional single-biomarker methods.